2018
DOI: 10.1016/j.ecolecon.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Certification of Semi-forest Coffee as a Land-sharing Strategy in Ethiopia

Abstract: We analyze whether private sustainability standards can improve the economic benefits from less intensified semi-forest coffee production in southwestern Ethiopia. We compare garden and semi-forest coffee systems, including non-certified and Rainforest Alliance certified semiforest coffee, and evaluate yields, returns to land, returns to labor and profits. We use original household-and plot-level survey from 454 households and 758 coffee plots derived from a household survey and Geographic Information Systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…These frameworks are designed to reduce atmospheric CO 2 emissions from deforestation and forest degradation, and may also result in co-benefits for biodiversity and other ecosystem services (Imai et al, 2014;Sullivan et al, 2017;Venter, 2014). Furthermore, several coffee certification programs aim to compensate farmers for loss of income when forest management is reduced in favor of the local biodiversity (Mitiku et al, 2018). However, premium coffee prices do often not sufficiently compensate for the related yield losses (Mitiku et al, 2017;Perfecto et al, 2005;Vanderhaegen et al, 2018), and in the unique case of Ethiopia, where coffee is a natural understorey species, coffee certification programs may actually be an incentive to convert natural forests into strongly managed yet certified coffee forests (Gove et al, 2008;Hylander et al, 2013).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…These frameworks are designed to reduce atmospheric CO 2 emissions from deforestation and forest degradation, and may also result in co-benefits for biodiversity and other ecosystem services (Imai et al, 2014;Sullivan et al, 2017;Venter, 2014). Furthermore, several coffee certification programs aim to compensate farmers for loss of income when forest management is reduced in favor of the local biodiversity (Mitiku et al, 2018). However, premium coffee prices do often not sufficiently compensate for the related yield losses (Mitiku et al, 2017;Perfecto et al, 2005;Vanderhaegen et al, 2018), and in the unique case of Ethiopia, where coffee is a natural understorey species, coffee certification programs may actually be an incentive to convert natural forests into strongly managed yet certified coffee forests (Gove et al, 2008;Hylander et al, 2013).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Even if in the future farmers would receive price differentiations based on quality, the very low yields of wild coffee compared to coffee agroforestry systems gives smallholder coffee farmers no option but to optimize quantity, not quality. Higher market prices for selling higher quality wild coffee cannot compete with the income smallholder farmers generate from higher yields in managed forests (Mitiku et al, 2017(Mitiku et al, , 2018. Such management intensification, however, may further jeopardize the conservation of the last remaining Ethiopian wild forests (Aerts et al, 2017) and their coffee genetic resources (Aerts et al, 2013).…”
Section: Implications and Concluding Remarksmentioning
confidence: 99%
“…The Specialty Coffee label is based on an evaluation of the organoleptic quality of coffee. Production methods, environmental conditions of the production areas, or trade properties are subjects of sustainable coffee certification schemes such as USDA Organic, Rainforest Alliance, Smithsonian Bird Friendly, Utz Certified or Fair Trade Certified (Mitiku et al, 2018). To evaluate if coffee samples can achieve the Specialty Coffee status, following attributes are evaluated: fragrance and aroma, flavor, aftertaste, acidity, body, balance, sweetness, clean cup, uniformity, overall appreciation, and defects (SCAA, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cocoa, coffee), besides improving productivity (Pinard et al 2014), are also found to contribute to farmers' livelihoods by providing NTFPs (Beyene et al 2019). Some studies reminded of the potential benefits that value chain improvements (Deans et al 2018), greening (Nhantumbo and Camargo 2016) and certification (Millard 2011;Mitiku et al 2018) of agroforestry plantations could bring for local communities, such as price premiums or improved benefit sharing. Certifications schemes were, however, documented as having mixed outcomes (see Section 4.3.5).…”
Section: Agroforestry Systemsmentioning
confidence: 99%